Campanian rudists (Hippuritida, Bivalvia) from Costa Rica (Central America). (16th June 2016) - Pons, Jose Maria; Vicens, Enric; Schmidt-Effing, Reinhard
Abstract: The Campanian rudist fauna identified from the localities Playa Panamá, Santa Rosa National Park, Colorado de Abangares, and Bolsón in Guanacaste Province, Costa Rica, is composed of the antillocaprinids Antillocaprina sp. aff. A. suboccidentalis Chubb, 1967, Antillocaprina sp. and Antillocaprinidae indet.; the multiple-fold hippuritids Barrettia monilifera Woodward, 1862, Parastroma trechmanni Chubb, 1967, and cf. Whitfieldiella gigas (Chubb, 1955); the plagioptychids Plagioptychus trechmanni Chubb, 1956, Plagioptychus sp. cf. P. zansi Chubb, 1956, Mitrocaprina costaricaensis new species, Mitrocaprina multicanaliculata Chubb, 1956, and Plagioptychidae indet.; and the radiolitids Radiolites sp. aff. R. multicostata (Adkins, 1930), Alencasterites new genus mooretownensis (Trechmann, 1924), Bournonia ? tetrahedron (Chubb, 1967), Chiapasella sp., Guanacastea costaricaensis new genus new species, cf. Potosites sp. aff. P. tristantorresi Alencáster and Pons in Pons et al., 2010, and aff. Thyrastylon sp. Although some differences in rudist diversity and sedimentary setting were observed among localities, most species indicate the same age for all occurrences, which correspond to the Campanian, probably mid-Campanian. Radiolitid specimens appear better preserved than those of other taxa and are thus discussed more in detail. Both the number of radiolitid genera exclusively known from the New World, and reasonable doubts about the correct attribution of some New World species to Old World genera, indicate important differences between rudist faunas at both sides of the Atlantic (Mediterranean and American Tethys, respectively) during the Late Cretaceous.